Editorial for the Special Issue "Antiprotozoal Activity of Natural Products" - Cecilia Baldassarri; Eleonora Spinozzi; Marta Ferrati; Paolo Rossi; Filippo Maggi; Riccardo Petrelli (MDPI AG, 2023)
Neglected tropical diseases (NTDs), a diverse group of infectious diseases, represent the leading cause of morbidity and mortality among the world's low-income populations [...]